Implementasi Program Go Green School Di Indonesia Sebagai Pembangunan Berkelanjutan - Layli Mumbaasithoh; Novi Dya Meylasari; Deden Nursidik; Susmawati Surya Asih (Jurnal Teknologi, 2022)
This study aims to determine the implementation of the Go Green school program in Indonesia. Data collection is carried out in several stages, namely searching for articles with the theme to be studied, and mapping topics. The step of analyzing the literature review method is by reading and re-exploring the points of thought on the same theme in several journals. to be able to add new ideas and opinions of the author regarding the topic to be raised. The author can also see the shortcomings of previous studies, so that the author can make improvements and more regular formulations. Energy security is an issue that has long been discussed by governments and even the global world. One of the government programs to maintain the resilience of the national country is the greening movement or what is often referred to as going green. The go green program is a government program that involves all elements of society including educational institutions in Indonesia. There are several elements in the go green program, in this study the author took three elements to be used as research material for the implementation of the go green program in schools, namely green transportation, green water, and green energy. The results of the study revealed that the implementation of the go green program in Indonesian Education institutions has not run optimally either in the school environment (adiwiyata school), or in the campus environment (Green campus). The low implementation of the go green program in schools is characterized by the low knowledge of teachers or principals related to knowledge based on the environment. At the university level, the implementation of the go green program is only found in a few universities and has not been comprehensive.